MODERN ASPECTS OF MOTIVATION AS AN ACTIVE PROCESS - Petrova, Sevdalina (E-Journal VFU, 2025)
The article presents a theoretical overview of the driving force in the performance of tasks - motivation. It has a defining role, both in the behavior of individual growth, and in the pursuit of achieving high results in a work environment.
Keywords: motivation; behavior; needs; goals